A double window state observer for detection and isolation of abrupt changes in parameters - Byrski, Jędrzej; Byrski, Witold (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a new method for diagnosis of a process fault which takes the form of an abrupt change in some real parameter of a time-continuous linear system. The abrupt fault in the process real parameter is reflected in step changes in many parameters of the input/output model as well as in step changes in canonical state variables of the system. Detection of these state changes will enable localization of the faulty parameter in the system.
Keywords: fault detection and isolation; exact state observer; parameter abrupt changes; derivative reconstruction; linear continuous systems